Nanoemulsion biopesticide formulated form Zingiber Purpureum extract and patchouli oil distillation waste for controlling bacterial leaf blight on rice - Dini Sundari; Woro Sri Suharti; Dina Istiqomah; Alya Nur Amila (Jurusan Agroteknologi, 2025)
Bacterial leaf blight, caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most destructive diseases in rice crops. This study aimed to assess the efficacy of nanoemulsion biopesticides derived from bangle extract (Zingiber purpureum) and patchouli oil distillation waste in controlling Bacterial Leaf Blight (BLB) in rice. The experiment used a Randomized Block Design with six replications, including a control, nanoemulsion biopesticide concentrations of 500, 1000, 1500, and 2000 ppm, and a bactericide as a positive control. The observed parameters included pathology (incubation period, disease intensity, infection rate, and area under disease progression curve) and agronomic traits (plant height, number of tillers, number of panicles, number of grains, 100-grains weight, root and shoot dry weight). The results showed that the application of biopesticide nanoemulsions, although it does not prolong the incubation period, was able to reduce disease intensity up to 8.7% compared to the control at a concentration of 2000 ppm and also lowered the rate of disease infection. The treatment did not have a significant effect on vegetative growth, however nanoemulsion biopesticides at concentrations above 1000 ppm increased production components, including grain number by 32% and 100-grain weight by 6.1% compared to the control. This study demonstrates that the nanoemulsion biopesticide formulation of bangle extract and patchouli oil distillation waste has the potential to be used as an environmentally friendly biopesticide to control Bacterial Leaf Blight while simultaneously increasing rice productivity. ABSTRAK Hawar daun bakteri yang disebabkan oleh Xanthomonas oryzae pv. oryzae merupakan salah satu penyakit paling merusak pada tanaman padi. Penelitian ini bertujuan mengevaluasi efektivitas biopestisida nanoemulsi berbahan ekstrak bangle (Zingiber purpureum) dan limbah penyulingan nilam dalam menekan hawar daun bakteri pada padi. Percobaan dilakukan dengan Rancangan Acak Kelompok yang terdiri atas enam perlakuan (kontrol, biopestisida nanoemulsi dengan konsentrasi 500, 1000, 1500, dan 2000 ppm, serta bakterisida sebagai kontrol positif) dengan enam ulangan. Parameter yang diamati meliputi aspek patologi (masa inkubasi, intensitas penyakit, laju infeksi, dan area under disease progression curve) serta aspek agronomi (tinggi tanaman, jumlah anakan, jumlah malai, jumlah biji, bobot 100 biji, bobot kering akar dan tajuk). Hasil penelitian menunjukkan bahwa meskipun tidak memperpanjang masa inkubasi, aplikasi nanoemulsi biopestisida tetapi mampu menekan intensitas penyakit mencapai 8.7% dibandingkan dengan kontrol pada konsentrasi 2000 ppm serta menurunkan laju infeksi penyakit. Perlakuan tidak menunjukkan perbedaan respon terhadap pertumbuhan vegetatif, namun biopestisida nanoemulsi dengan konsentrasi di atas 1000 ppm meningkatkan komponen produksi berupa jumlah biji sebesar 32% dan bobot 100 biji mencapai 6,1% dibandingkan dengan kontrol. Penelitian ini menunjukkan bahwa formulasi biopestisida nanoemulsi ekstrak bangle dan limbah nilam berpotensi digunakan sebagai biopestisida ramah lingkungan untuk mengendalikan hawar daun bakteri sekaligus meningkatkan produktivitas padi.